Li47B3P14N42—A Lithium Nitridoborophosphate with [P3N9]12−, [P4N10]10−, and the Unprecedented [B3P3N13]15− Ion. (29th March 2017) - Bertschler, Eva‐Maria; Bräuniger, Thomas; Dietrich, Christian; Janek, Jürgen; Schnick, Wolfgang
Abstract: Li47 B3 P14 N42, the first lithium nitridoborophosphate, is synthesized by two different routes using a Li3 N flux enabling a complete structure determination by single‐crystal X‐ray diffraction data. Li47 B3 P14 N42 comprises three different complex anions: a cyclic [P3 N9 ] 12−, an adamantane‐like [P4 N10 ] 10−, and the novel anion [P3 B3 N13 ] 15− . [P3 B3 N13 ] 15− is the first species with condensed B/N and P/N substructures. Rietveld refinement, 6 Li, 7 Li, 11 B, and 31 P solid‐state NMR spectroscopy, FTIR spectroscopy, EDX measurements, and elemental analyses correspond well with the structure model from single‐crystal XRD. To confirm the mobility of Li + ions, their possible migration pathways were evaluated and the temperature‐dependent conductivity was determined by impedance spectroscopy. With the Li3 N flux route we gained access to a new class of lithium nitridoborophosphates, which could have a great potential for unprecedented anion topologies with interesting properties.